Pathogenicity of Lecanicillium longisporum (Ascomycota: Hypocreomycetidae) on the aphid Cinara pini (Hemiptera: Lachnidae) in laboratory conditions - Amir Hossein Nazemi; Gholamhossein Morravej; Javad Karimi; Reza Talaei-Hassanloui (Journal of Crop Protection, 2014)
The aphid species, Cinara pini (Linnaeus, 1758) reported in our previous work as a new aphid on pinus trees for Iran, was described using the classic method and through analysis of COI gene sequence. In the next step, we addressed the efficiency of the entomopathogenic fungus, Lecanicillium longisporum (Zimm.) Zare and Gams strain LRC 190, on the aphid. The fungus was administered to the second instar nymphs and adults using topical application procedure. The results indicated that the entomopathogen caused 90% mortality in adults over seven days at a concentration of 108 spores/ml, while the same control level was achieved for nymphs by 8 × 107 spores/ml. The LC50 values were obtained as 1.2 × 106 and 6.9 × 105 spores/ml for adults and nymphs, respectively. The present study suggests that the entomopathogenic fungus, L. longisporum could be considered as a potential candidate in biocontrol programs of C. pini. This is the first report on the pathogenicity of L. longisporum on C. pini.